Quantum defects in fluorescent carbon nanotubes for sensing and mechanistic studies - Spreinat, Alexander; Dohmen, Maria M.; Lüttgens, Jan; Herrmann, Niklas; Klepzig, Lars F.; Nißler, Robert; Weber, Sabrina; Mann, Florian A.; Lauth, Jannika; Kruss, Sebastian (The journal of physical chemistry. C, Energy, materials, and catalysis, 2021)
Single-wall carbon nanotubes (SWCNT) fluoresce in the near-infrared (NIR) region and have been assembled with biopolymers such as DNA to form highly sensitive molecular (bio)sensors. They change their fluorescence when they interact with analytes. Despite the progress in engineering these sensors, the underlying mechanisms are still not understood. Here, we identify processes and rate constants that explain the photophysical signal transduction by exploiting sp3 quantum defects in the sp2 carbon lattice of SWCNTs. As a model system, we use ssDNA-coated (6,5)-SWCNTs, which increase their NIR emission (E11, 990 nm) up to +250% in response to the important neurotransmitter dopamine. In contrast, SWCNTs coated with DNA but with a low number of NO2-aryl sp3 quantum defects decrease both their E11 (−35%) and defect-related E11* emission (−50%) at 1130 nm. Consequently, the interaction with the analyte does not change the radiative exciton decay pathway alone. Furthermore, the fluorescence response of pristine SWCNTs increases with SWCNT length, suggesting that exciton diffusion is affected. The quantum yield of pristine (6,5)-SWCNTs increases in response to the analyte from 0.6 to 1.3% and points to a change in non-radiative rate constants. These experimental results for dopamine and other analytes are explained by a Monte Carlo simulation of exciton diffusion, which supports a change in two non-radiative decay pathways together with an increase in exciton diffusion (three-rate constant model). The combination of such SWCNTs with defects and without defects enables the assembly of ratiometric biosensors with opposing responses at different wavelengths. In summary, we demonstrate how perturbation of a nanomaterial with quantum defects reveals the photophysical mechanism and reverses optical responses of biosensors.
Gesehen am 05.11.2021